2005
DOI: 10.1002/ffj.1653
|View full text |Cite
|
Sign up to set email alerts
|

Volatile flavour components of dry milky mushrooms (Calocybe indica)

Abstract: Drying of MushroomsFresh mushrooms with a moisture content of 85-90% were air-dried at 40-45°C to a final moisture content of 10%. The dried mushrooms were later used for the extraction of flavour compounds. Isolation of Volatile CompoundsFresh (300 g) and dried (30 g) mushrooms were cut into small pieces and homogenized in a Waring blender (Braun, Model-MX-32-2, Germany) at low speed with 600 ml distilled water for 2 min. The homogenate was subjected to simultaneous distillation and solvent extraction under r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
2
12
0
4
Order By: Relevance
“…The high ash content of Moringa olefera (38.53%) when compare with low ash values of Solanium marcro carpon (6.45%) which is the least of all the vegetables investigated was an indication that there were more minerals in Moringa olefera, Ocimum gratissimum, Corchorus telfaria, Telfairia occidentalis, Talinum triangulare and Amaranthus hybridus, than in Solanium marcro carpon, Vernonia amygdalina, Murraya koenigii and Telfairia occidentalis. The values of ash content obtained in this studied were comparable to those reported for some vegetables in other similar studies such as A. hybridus, C. peps and G. africana (Chandravadana et al, 2005).…”
Section: Resultssupporting
confidence: 89%
“…The high ash content of Moringa olefera (38.53%) when compare with low ash values of Solanium marcro carpon (6.45%) which is the least of all the vegetables investigated was an indication that there were more minerals in Moringa olefera, Ocimum gratissimum, Corchorus telfaria, Telfairia occidentalis, Talinum triangulare and Amaranthus hybridus, than in Solanium marcro carpon, Vernonia amygdalina, Murraya koenigii and Telfairia occidentalis. The values of ash content obtained in this studied were comparable to those reported for some vegetables in other similar studies such as A. hybridus, C. peps and G. africana (Chandravadana et al, 2005).…”
Section: Resultssupporting
confidence: 89%
“…Available carbohydrate content in oyster varieties compared well, while the content was relatively high(6.38g%) in Calocybe indica. Mushrooms are valuable sources of dietary fibre 12 . Dietary fiber content of mushrooms, in present study, was found to be in a range of 0.58-1.11g%.…”
Section: Resultsmentioning
confidence: 99%
“…C. chrysenteron exhibits, in addition to its characteristic flour-like odor, a fruity note (Breitenbach und Kränzlin 1991). Out of the Calocybe species that do not smell like cucumber, the aroma profile of C. indica was characterized by Venkateshwarlu et al (1999) and Chandravadana et al (2005). In the latter study, 20 aroma active compounds were identified, but no flour-or cucumber-like flavor was detected.…”
Section: Discussionmentioning
confidence: 96%
“…In our study of the volatilome of C. gambosa, seven typical C 8 -compounds were detected in the extracts of the fresh fruiting bodies, which were absent in the extracts of the dried fruiting bodies. In C. indica, a mild air-drying process at 40-45°C led to reduced concentrations of alcohols and aldehydes (Chandravadana et al 2005). Ashmore et al (2014) observed that the concentrations of C 8 -compounds, except for oct-1-en-3-one, decreased in fruiting bodies of A. bisporus during drying or boiling.…”
Section: Discussionmentioning
confidence: 98%